Cover Feature: Elucidating the Promotional Effect of Cerium in the Dry Reforming of Methane (2/2021). Issue 2 (23rd December 2020) - Rodriguez‐Gomez, Alberto; Lopez‐Martin, Angeles; Ramirez, Adrian; Gascon, Jorge; Caballero, Alfonso
Abstract : The Cover Feature depicts, in a comic book format, the cooperation of nickel and ceria for the conversion of methane and carbon dioxide into syngas, a promising route to address the excess greenhouse gas output. In their Full Paper, a collaboration between the University of Seville and the King Abdullah University of Science and Technology, A. Rodriguez‐Gomez et al. apply a combination of advanced characterization techniques to elucidate the role of ceria, which has been commonly found to improve the stability of reforming catalysts, as a promoter in the dry reforming of methane. By enhancing the carbon dioxide activation, ceria led to improve the H2 /CO ratio and carbon balance while addressing the main obstacle of this reaction at the industrial level, the formation of coke. Cover artwork was designed by Sandra Ramirez Cherbuy. More information can be found in the Full Paper by A. Rodriguez‐Gomez et al.